2017
DOI: 10.1002/erv.2544
|View full text |Cite
|
Sign up to set email alerts
|

Improving Inhibitory Control Abilities (ImpulsE)—A Promising Approach to Treat Impulsive Eating?

Abstract: Although there is preliminary evidence that inhibitory control training improves impulsive eating, less is known about the effects on eating behaviour and weight loss in clinical samples. Sixty-nine treatment-seeking adults with obesity (binge-eating disorder 33.3%; other specific feeding and eating disorders 40.6%) were randomly blockwise allocated to ImpulsE, an intervention to improve inhibitory control and emotion regulation abilities or a guideline-appropriate cognitive behavioural therapy (CBT)-based tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 68 publications
1
44
0
Order By: Relevance
“…Taking these comparisons into account, it seems that IMPULS might be as effective as a CBT-based treatment as usual. This assumption is also in line with the conclusion that Preuss et al [37] have drawn from their RCT concerning an impulsivity-based treatment in obese patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Taking these comparisons into account, it seems that IMPULS might be as effective as a CBT-based treatment as usual. This assumption is also in line with the conclusion that Preuss et al [37] have drawn from their RCT concerning an impulsivity-based treatment in obese patients.…”
Section: Discussionsupporting
confidence: 76%
“…Food cue exposure in virtual reality was also superior in reducing BE as a second-level treatment compared with ongoing CBT in a sample consisting of patients with bulimia nervosa or BED [36]. In a sample of obese patients with an included subgroup of patients with BED (33%), a group intervention delivering strategies concerning inhibitory control and emotion regulation combined with a computer-based training of inhibitory control was comparable with usual CBT concerning overeating [37]. To summarise, self-control strategies and food cue exposure seem fruitful to reduce BE and might be helpful in patients with BED.…”
Section: Introductionmentioning
confidence: 99%
“…While individuals would be recommended to avoid highly processed foods, treatment based on this new model would continue to discourage individuals from restricting healthy foods, to prevent them from reaching a state of semi‐starvation. Target 3: To counteract habit formation that entrenches stimulus response association between food cues and eating, another addition may be to add treatments, which target impulsivity and habitual patterns of responding. Pilot studies for computerized approaches such as stop signal and go/no‐go training have potential . Moreover, research in progress using these computerized approaches, as well as virtual reality cue exposure and emotional regulation video game training are being modified to become more accessible, more rewarding, and more personalized .…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…Some researchers have proposed that OB and attention deficit/hyperactivity disorder (ADHD) might share a common neurocognitive phenotype, characterized by deficits in hot executive functions, associated with impaired inhibitory control and impulsivity have (Lavagnino, Arnone, Cao, Soares, & Selvaraj, 2016;Preuss, Pinnow, Schnicker, & Legenbauer, 2017). Previous studies have observed that people with OB performed significantly worse on tasks assessing domains such as interference control, memory span length, and reward sensitivity in comparison with healthy weight controls (Aiello et al, 2018;Fagundo et al, 2012;Farooq, Gibson, Reilly, & Gaoua, 2018;Song et al, 2016).…”
mentioning
confidence: 99%
“…Previous studies have observed that people with OB performed significantly worse on tasks assessing domains such as interference control, memory span length, and reward sensitivity in comparison with healthy weight controls (Aiello et al, 2018;Fagundo et al, 2012;Farooq, Gibson, Reilly, & Gaoua, 2018;Song et al, 2016). Specifically, interference control tasks assess the capacity of suppressing inappropriate actions that could interfere with achieving a long-term goal, and evidence suggests that some individuals with OB display difficulty inhibiting automatic or model-free behaviour (MacLeod, 1991;Preuss et al, 2017). Lastly, there is increasing evidence to support that OB has a detrimental effect on overall attentional capacity (Cook et al, 2017;Fagundo et al, 2012;Siervo et al, 2011;Tsai, Huang, & Tsai, 2017).…”
mentioning
confidence: 99%